PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PENINGKATAN KUALITAS PENGETAHUAN(VALUE ADDED KNOWLEDGE} PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH GRESIK - Wasti Reviandadani (Jurnal Riset Entrepreneurship, 2020)
This study examines the impact of social media on improving the quality of student knowledge, the types of social media studied are Facebook, Instagram, Twitter, and Youtube, at Muhammadiyah Gresik University students, this study is a quantitative study with the help of program analysis tools such as version 17.0, taking techniques Data with purposive sampling, the results of this study are Facebook and Twitter have a negative influence on the quality of knowledge, YouTube and Instagram have a positive influence on improving the quality of student knowledge